Comienza el largo camino del exilio : (Febrero 1939) / [redacción Javier Redondo... (et al.)] - Redondo Rodelas, Javier (La guerra civil Española mes a mes ; 34)
Ejemplar encuadernado al revés | Contiene "Semblanzas" de : Diego Martínez Barrio, Sánchez-Albornoz, José Ungría, Enrique Suęr, Josep Pla, Rafael Sánchez Mazas, Antonio Machado, Mourlane Michelena